Efektifitas Penerapan Model Tpack Dalam Meningkatkan Minat Belajar Siswa Kelas Vii Mts Hidayatul Insan Palangka Raya - Jasiah J; Futihatu Saidah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the effectiveness of the implementation of the TPACK (Technological Pedagogical Content Knowledge) model in improving the learning interest of grade VII students at MTs Hidayatul Insan Palangka Raya. The background of this study is based on the challenges faced in improving students' learning interest, which requires an innovative approach in learning. The methods used are qualitative and quantitative approaches, with data collection through observation, interviews, and questionnaires involving 20 questions on learning interest indicators. The results of the study showed that the implementation of the TPACK model succeeded in increasing students' learning interest, with 75% of respondents agreeing with the use of this model. The conclusion of this study confirms that the integration of technology in learning can create a more interesting and effective learning atmosphere for students, thus supporting the development of teachers' pedagogical competence in the digital era.